Alternativas pedagógicas em uma disciplina de Mestrado de um curso de odontologia: um projeto exploratório - Prado, Andréa Sales do (2005)
The purpose of the present work is to present an exploratory study of alternative pedagogical practices performed through strategies based on propositions, like PBL (Problem Basic Learning), Case Study and Work with small groups, aiming to improve the students learning ability in Biostatistics (a subject of a Master s degree in Dentistry in the Universidade de São Paulo). In general, Dental schools keep a lot of aspects from the traditional paradigm, such as: the teaching focused on the professor, the curriculum fragmented in subjects, basic, pre-clinical and clinical, which will be further integrated, a political pedagogical project which is not developed by the right professionals, the lack of articulation and integration of theory and practice, and the students passive behavior. Those aspects concern not only a change in the methodology, but also other questions, like the meaning of teaching and learning, the development of competences and abilities, the teachers professionalization, the teachers continued education process, the collective construction of a political pedagogical project and the possibility of emancipation through a course with formative education. Given the nature of the problem, the most suitable methodology was the qualitative one, because it allowed the understanding and the discussion on the meaning of a change in a teaching paradigm in real situations involving teacher and students. Understanding not only the results but also the sense of those activities was essential to try to solve the proposed questions. The research was well conducted by a participant professor and its result was positive: the students learning was improved by a new proposition made by the professor who, in turn, thought over his pedagogical practice and used techniques in favor of the students participation, self education and cooperative learning.